Migrations, Care Work and Social Risks: The Contradictions of Welfare in the Context of COVID-19 - Martínez-Buján, Raquel; Moré Corral, Paloma (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
This article explores the impact of the COVID-19 pandemic on the working conditions of migrant care workers for the elderly and dependent people in Spain. Through an exploitation of data from the Spanish Labor Force Survey, the article analyzes the effects of the health crisis on the precariousness (measured through unemployment and temporary employment). The study of this situation of inequality is articulated linking the characteristics of the public model of long-term care with cultural values that place migrant women in these activities. This context of social risk has highlighted the contradictions that exist in the welfare system: care workers suddenly become essential while they are excluded from access to basic social rights.